2023
DOI: 10.3390/diseases11010029
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium in Osteoporosis, and the Role of Bone Turnover Markers: A Narrative Review of Recent Data from RCTs

Abstract: Osteoporosis is a common disease, defined primarily by a low measured bone density, which is associated with an increased risk of fragility fractures. Low calcium intake and vitamin D deficiency seem to be positively correlated with the prevalence of osteoporosis. Although they are not suitable for the diagnosis of osteoporosis, the biochemical markers of bone turnover can be measured in serum and/or urine, enabling the assessment of the dynamic bone activity and the short-term effectiveness of the osteoporosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…This indicated that the glucose effects were primarily due to direct effects of dietary vitamin D and not to obesity or insulin resistance related to fat accumulation changes. While we did not see differences in bone mineral content across the treatment groups, this is expected given that bone mineral content changes would likely require more than 12 weeks of treatment [43]. Due to issues with sample storage during the pandemic, we were not able to determine 25-OHD and calcium levels from the serum of the various dietary vitamin D cohorts.…”
Section: Discussionmentioning
confidence: 94%
“…This indicated that the glucose effects were primarily due to direct effects of dietary vitamin D and not to obesity or insulin resistance related to fat accumulation changes. While we did not see differences in bone mineral content across the treatment groups, this is expected given that bone mineral content changes would likely require more than 12 weeks of treatment [43]. Due to issues with sample storage during the pandemic, we were not able to determine 25-OHD and calcium levels from the serum of the various dietary vitamin D cohorts.…”
Section: Discussionmentioning
confidence: 94%
“…Vitamin D has been shown to play a fundamental role in calcium and phosphate homeostasis, furthermore, serum levels of vitamin D are positively correlated with BMD values ( 40 ). In contrast, vitamin D deficiency causes a reduction of BMD, increasing the risk of bone fractures in the elderly ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and vitamin D are crucial for the preservation of bone health, and there appears to be a positive correlation between vitamin D deficiency and the occurrence of osteoporosis. 18 It is reported that deficiency in vitamin D could be a risk factor for the development of dry eye syndrome and deficiency in vitamin D could impair tear production. 19 Tear production measured by Schirmer test was also found to be decreased in patients with low serum 25(OH) D levels which is the active metabolite of Vitamin D. 20 Our results showing lower tear production in patients with osteoporosis support these findings.…”
Section: Discussionmentioning
confidence: 99%